Brain white matter development in 8-year-old children is associated with maternal mental health during pregnancy - Huang, Yali; Koscik, Timothy R.; Andres, Aline; Bellando, Jayne; Glasier, Charles M.; Ram, Adhitya; Ou, Xiawei (Frontiers in Human Neuroscience, 2025)
BackgroundMaternal mental health during pregnancy can influence fetal brain development, yet its long-term effects remain unclear. This study investigates the association between prenatal maternal depression and anxiety symptoms and white matter microstructure in the limbic system of 8-year-old children.MethodsFifty-one healthy pregnant women and typically developing 8-year-old children dyads were included in this prospective and longitudinal study. Maternal depression and anxiety symptoms were assessed at 12, 24, and 36 weeks of gestation using the Beck Depression Inventory-II (BDI-II) and State–Trait Anxiety Inventory (STAI). Their children underwent a brain MRI examination at age 8 years with multi-shell diffusion imaging analyzed using diffusion tensor imaging (DTI), diffusional kurtosis imaging (DKI), and neurite orientation dispersion and density imaging (NODDI) models for a multi-aspect evaluation of microstructural development. Key diffusion metrics (FA: fractional anisotropy; MD: mean diffusivity; AD: axial diffusivity; RD: radial diffusivity; MK: mean kurtosis; AK: axial kurtosis; RK: radial kurtosis; NDI: neurite density index; ODI: orientation dispersion index; FWF: free water fraction) were extracted from the limbic system white matter structures including cingulum, fornix, and uncinate fasciculus, which are closely associated with emotional and motivational processes.ResultsHigher maternal depression symptom scores were associated with lower FA (R = –0.3126, p = 0.0305, in CGH.R; R = –0.3025, p = 0.0366, in FXC.R) and MK (R = –0.3284, p = 0.0227, in CGG.R) and higher MD (R = 0.2879, p = 0.0472, in CGH.R) and RD (R = 0.3451, p = 0.0163, in CGH.R; R = 0.3456, p = 0.0161, in FXC.R) in predominately right-hemisphere limbic tracts. Higher maternal anxiety symptom scores were associated with increased MD (R = 0.2897, p = 0.0458, in FXC.L; R = 0.2859, p = 0.0488, in UF.L) and RD (R = 0.3168, p = 0.0283, in FXC.L), decreased NDI (R = –0.3787, p = 0.0079, in FXC.L; R = –0.3422, p = 0.0173, in UF.R), and increased AK (R = 0.3154, p = 0.029, in UF.L) in predominately left-hemisphere limbic tracts.ConclusionOur findings suggest that maternal depression and anxiety during pregnancy may have long-lasting impacts on offspring white matter microstructure maturation in the limbic system. This highlights the need for prenatal mental health screening and potential interventions to promote brain development and support optimal neurodevelopmental outcomes in children.